EAPH-03. FINAL RESULTS OF THE PHASE II, SINGLE ARM TRIAL OF IRINOTECAN AND CISPLATIN IN CHILDREN WITH HIGH-RISK GLIAL TUMORS. Issue 2 (22nd June 2018) - Cruz, Ofelia; Caloretti, Victoria; Suñol, Mariona; de Torres, Carmen; Morales, Andres; Guillen, Antonio; Muchart, Jordi; Rodriguez, Eva; Celis, Veronica; Salvador, Hector; Vinent, Joan; Perez-Jaume, Sara; et al.
Abstract: We conducted an open label, single arm phase II clinical trial with with irinotecan and cisplatin (I/C) for pediatric patients with glial tumors (EudraCT:2009-010742-59). METHODS: Patients diagnosed with high-risk (HR) gliomas at diagnosis (HGG, ependymomas, DIPG, or HR-LGG) received sixteen weekly outpatient iv. cycles of Cisplatin(30mg/m2) and Irinotecan(65mg/m2). Malignant gliomas received radiation at progression. Objective response was assessed with MRI plus volumetric analysis. Clinical and neurological changes were assessed. RESULTS: Since November/2009 until December/2012, 39 patients (66, 7% females), aged 7m-17y (mean=84-months), diagnosed with DIPG(n=7), HGG(n=5), anaplastic-ependymoma(n=6), atypical neurocytoma(n=1), LGG n=20: Pilocytic Astrocytoma(n=7), Pilomyxoid A.(n=1), Astrocytoma NOS(n=5), Grade-II astrocytoma (n=2), Ganglioglioma(n=2), LGG-NF1(n=3) were included. Most frequent events were nausea/vomiting, mostly grade 1–2, only 5/39 grade >2; 17 patients (43, 6%) developed grade-1 diarrhea. At the end of follow-up 3/31 patients developed hypoacusia, all grade 1 (9, 7%). Five (45.5%) patients with HGG, 1 relapsed HGG(100%), 7 DIPG(100%) and 3 LGG(15.0%) progressed during treatment, ending prematurely the study. Objective response rate (ORR) at the end of therapy (week 21), was by ITT / PP, of 54, 4% for HGG, 0% for DIPG, and 85% for HR-LGG After a median follow-up time of 67.5 months, OS/EFS was 0/0% for relapsed HGG and DIPG, 62%/23% for High-grade glial tumors, and 95%/43% for HR-LGG. Radiation was avoided in 19/20 HR-LGG patients. CONCLUSION: The I/C regimen was acceptably tolerated and shows activity for some children with HR-gliomas, mainly HR-LGG.